ANALISIS RETURN 3 INDIKATOR TEKNIKAL UNTUK PAIR USD-JPY TAHUN 2013 - Marcella Hartanto (Jurnal Universitas Paramadina, 2014)
This study aims to read and compare the price movements of returntransactions generated by each indicator Parabolic SAR, Bollinger Bandsand Stochastic Oscillator , and a combination. This study form based on thesimulation of trading and trading plan that has been created based on eachindicator and a combined indicator. Trading plan in the form of this tradingsystem will be implemented in a software Victory Trader 4 . The simulationresults using the Parabolic SAR indicator trading generates a return of 3,255pips of 17 transactions during the year 2013, while trading simulation usingStochastic Oscillator indicator generates a return of 5619 pips of 19transactions . Simulation results for the indicator Bollinger Bands tradinggenerate 1661 pips of 14 transactions , while trading simulation with acombined indicator generates a return of 1152 pips of 3 transactions .Indicator Stochastic Oscillator generates the greatest return than otherindicators. The parabolic SAR indicator, the Stochastic Oscillator andBollinger Bands should not be combined into a single instrument, becausethe three indicators do not give a reversal signal simultaneously. The lessonslearn from the simulation results is that we can not use more than twoindicators, due to the potential refraction information.